Continuous estimation of coseismic and early postseismic slip phenomena via the GNSS carrier phase to fault slip approach: a case study of the 2011 Tohoku-Oki sequence - Yusuke Tanaka; Yusaku Ohta; Shin’ichi Miyazaki (figshare, 2022)
Abstract The transition process from coseismic to early postseismic phenomena within a half-day remains a significant topic for understanding the slip budget and friction properties of the fault. However, the investigation of this phase has undergone limited advancement. This is mainly due to the lack of precision pertaining to the Global Navigation Satellite System (GNSS) analysis caused by difficulty of separation between fault slip and other unknown parameters such as tropospheric delay. Therefore, we propose an alternative approach (phase-to-slip; PTS) that detects fault slip directly from GNSS carrier phase variation without conventional positioning. Since the PTS simultaneously estimates fault slip and other unknowns, we can quantitatively evaluate their separation accuracy and contribution in the estimation. This study attempts to continuously estimate the coseismic and early postseismic slip of the 2011 Tohoku-Oki sequence using the PTS method. We analyzed 1-Hz carrier phase data for approximately 2 h before and after the mainshock origin (2011/03/11/05:46UTC). As a result, we successfully obtained the coseismic slip of the Mw9.0 mainshock and two major aftershocks in the off-Ibaraki (Mw7.8) and off Iwate (Mw7.4) regions. For all three events, the estimated slip distribution, equivalent moment magnitude, and calculated displacement field well agreed with those from the conventional positioning. Additionally, our results suggest postseismic slip mainly in the downdip area adjacent to the mainshock rupture. We obtained three major slip areas around the downdip region near Aomori, Iwate, and Miyagi. The estimated slip amount reaches approximately 0.1–0.2 m in 34 min immediately after the mainshock. The equivalent seismic moment of the slip areas near Iwate and Miyagi were approximately Mw7.4. This amount is similar or slightly greater than the estimations based on conventional positioning. Significant overlap is observed in the locations of the slip areas. In this manner, PTS continuously detected a series of coseismic and early postseismic slips with timescale ranging from a few minutes to an hour. Our results demonstrate the capability of the PTS method for broadband fault slip monitoring and its potential contribution to the investigation of early postseismic phenomena.
Keywords: Biophysics; 29999 Physical Sciences not elsewhere classified; Biotechnology; 59999 Environmental Sciences not elsewhere classified; 69999 Biological Sciences not elsewhere classified; 19999 Mathematical Sciences not elsewhere classified; Science Policy